Polymerization of acrylonitrile in the presence of functional azo-initiator 2,2'-azobis[2-methyl-?-hydroxy-oligo(oxyethylene) propionate] - Wiśniewska, E.; Pabin-Szafko, B. (Polimery, 2022)
The course of acrylonitrile (AN) polymerization initiated with oligomeric azoester 2,2'-azobis[2-methyl-?-hydroxy-oligo(oxyethylene) propionate] [AIB-OOE(400)] in N,N-dimethylformamide (DMF) solutions, at temp. 60°C and in the whole possible to study range of monomer - solvent mixture compositions (expressed by the monomer mole fraction xM), was characterized (Fig. 1-4). The determined kinetic parameters of the reaction, i.e. rate constant (2kdf) and efficiency (f) of initiation, polymerization rate (overall rate constant K~), polymerizability (?) and indirectly also the propagation rate constant (kp) illustrate the variability of polymerization conditions. They are homogeneous, transient and heterogeneous (Table 2 and 3) being functions of xM (concentration effect of polymerization). A hypothesis was proposed that selective solvation of initiator by monomer and solvent has got further consequences expressed as changes of reactivity of growing radicals. The studied process of acrylonitrile polymerization in the presence of functional initiator (azoester) was compared with AN polymerization initiated with conventional initiator 2,2'-azobisisobutyronitrile (AIBN), carried out in similar conditions. The different kinetic characteristics of both polymerizations [particularly for xM>0.4, when a significant acceleration of the process takes place when AIB-OOE(400) initiator is used] suggest the possibility of preliminary arrangement of monomer, favored by mutual interactions of chemical groups in monomer and initiator.